Erythropoietin accelerates the revascularization of transplanted pancreatic islets - Menger, Maximilian M. (Br J Pharmacol, 2020)
BACKGROUND AND PURPOSE: Pancreatic islet transplantation is a promising therapeutic approach for Type 1 diabetes. A major prerequisite for the survival of grafted islets is a rapid revascularization after transplantation. Erythropoietin (EPO), the primary regulator of erythropoiesis, has been shown to promote angiogenesis. Therefore, we investigated in this study whether EPO improves the revascularization of transplanted islets. EXPERIMENTAL APPROACH: Islets from FVB/N mice were transplanted into dorsal skinfold chambers of recipient animals, which were daily treated with an intraperitoneal injection of EPO (500 IU·kg(−1)) or vehicle (control) throughout an observation period of 14 days. In a second set of experiments, animals were only pretreated with EPO over a 6‐day period prior to islet transplantation. The revascularization of the grafts was assessed by repetitive intravital fluorescence microscopy and immunohistochemistry. In addition, a streptozotocin‐induced diabetic mouse model was used to study the effect of EPO‐pretreatment on the endocrine function of the grafts. KEY RESULTS: EPO treatment slightly accelerated the revascularization of the islet grafts. This effect was markedly more pronounced in EPO‐pretreated animals, resulting in significantly higher numbers of engrafted islets and an improved perfusion of endocrine tissue without affecting systemic haematocrit levels when compared with controls. Moreover, EPO‐pretreatment significantly accelerated the recovery of normoglycaemia in diabetic mice after islet transplantation. CONCLUSION AND IMPLICATIONS: These findings demonstrate that, particularly, short‐term EPO‐pretreatment represents a promising therapeutic approach to improve the outcome of islet transplantation, without an increased risk of thromboembolic events.